1962
DOI: 10.1139/v62-109
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution From Sodium Hypochlorite Solutions

Abstract: The rates of oxygen evolution from carefully purified solutions of sodium hypochlorite have been measured. Methods of purification are described, and it is found that substantially the same rate is observed regardless of the method of purification. The rate of oxygen evolution is proportional to the square of the concentration of hypochlorite ions. The effect of temperature and ionic strength are examined. The rate constant is 7.5X1OP6 (g-rn~l/l.)-~(min)-I a t 60" C and an ionic strength of 3.5; the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…As a comparison, the rate constant for the slow first step in the formation of chlorate, found to occur in two steps via ClO 2 – , was 0.95 M –1 s –1 at 40 °C. Two more papers were later published , by the same author and a co-worker. Both of these papers were focused on attempts to completely remove any impurities, such as of copper, that might catalyze the formation of oxygen.…”
Section: Selectivity For Oxygen and Chlorine Evolution In Chlor-alkal...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a comparison, the rate constant for the slow first step in the formation of chlorate, found to occur in two steps via ClO 2 – , was 0.95 M –1 s –1 at 40 °C. Two more papers were later published , by the same author and a co-worker. Both of these papers were focused on attempts to completely remove any impurities, such as of copper, that might catalyze the formation of oxygen.…”
Section: Selectivity For Oxygen and Chlorine Evolution In Chlor-alkal...mentioning
confidence: 99%
“…Both of these papers were focused on attempts to completely remove any impurities, such as of copper, that might catalyze the formation of oxygen. Indeed, in the later paper of Lister and Petterson, it was concluded that the uncatalyzed decomposition of hypochlorite is of second order in OCl – , with a rate constant of 7.5 × 10 –6 M –1 min –1 at an ionic strength of 3.5 and 60 °C. On the basis of an evaluation of activation energies, and comparison with the chlorate formation reaction, it was suggested that the two reactions had activated complexes with the same stoichiometry, Cl 2 O 2 2– , but with different arrangements.…”
Section: Selectivity For Oxygen and Chlorine Evolution In Chlor-alkal...mentioning
confidence: 99%
“…The other way for hypochlorite decomposition is the formation of O 2 (Lister and Petterson, 1962). The decomposition may be catalyzed by transition-metal ions such as Ni(II), Cu(II), and Fe(III) (Gordon and Bubnis, 2000).…”
Section: Substitution (Equation 11) (11)mentioning
confidence: 99%
“…Oxides of nickel, cobalt, and copper are very effective; their catalytic activity decreases in that order. The catalytic action of manganese, iron, lead, and tin has been demonstrated, but is at least one order of magnitude smaller [53], [177]. Autocatalytic decomposition is also possible, but its extent is negligible at ambient temperature [177], [178].…”
Section: Loss Reactionsmentioning
confidence: 99%